HEARING IN THE GIANT SEA TURTLE, Chelonia mydas - Ridgway, Sam H. (1969)
Measurement were made of the cochlear potentials in three specimens of the giant sea turtle, Chelonia mydas, in response to both aerial and mechanical stimulation of the ear. The results show maximum sensitivity in the region of 300 to 400 Hz, with a rather rapid decline in sensitivity for lower and especially for higher tones. The upper limit for the observation of cochlear potentials without injury is 2000 Hz, and a practical limit of usefulness of this ear is probably about 1000 Hz.